Émissions de CO2 liées à la mobilité domicile-travail : une double lecture par le lieu de résidence et le lieu de travail des actifs à Lyon et à Lille - Louafi Bouzouina; Bernard Quetelard; Florence Toilier (Développement Durable et Territoires)
In a context of strong financial, environmental and energy constraints, to reduce the consumption of fossil energy in the field of transport becomes not only an emergency but imposes a paradigm shift in terms of transport policy. It is not sufficient today to improve the supply, to target travel demand and stimulate behavior change becomes necessary. In particular, commuting structuring mobility practices also strongly contributes to CO2 emissions. By combining census data and household travel surveys in two different urban areas, Lille and Lyon, our aim is first to measure the CO2 emissions related to commuting and secondly, to identify the most emitting CO2 zone from the point of view of the residences and jobs location in the two contexts. The results are discussed in a perspective of enlargement and improvement of collective approaches (Company or Inter-company Travel Plans) focused on home-work migration. They highlight some explaining factors but also the role that could take the urban form in the reduction of CO2 emissions, through the centralities and the functional specialization.